Teachers’ Strategies in Teaching English Vocabulary by Using the EWA Application - Kadir, Meymin; Mamu, Rahmawaty; Pilongo, Jolanda H.D. (Transbahasa, 2024)
This study investigates teachers' strategies for applying the EWA application in the classroom. Using qualitative methods, data were collected from teachers through observation, interviews, and documentation. The documentation consisted of materials from teachers who used the EWA application, while structured interviews provided detailed insights into their experiences teaching English vocabulary with the app. The results highlight two main strategies: Cooperative Learning and the Clustering Method. In Cooperative Learning, students share and exchange vocabulary, promoting peer-to-peer learning. The Clustering Method involves using pictures to prompt students to identify related vocabulary, enhancing visual learning. Both strategies actively engage students and make learning enjoyable due to the EWA app's interactive and visually appealing features. However, internet connectivity issues pose challenges. Teachers utilize LCD projectors and computer labs to overcome these, ensuring that lessons proceed smoothly. This study concludes that using Cooperative Learning and the Clustering Method with the EWA application can significantly enhance student participation and enjoyment in learning English vocabulary.